Assessing the knowledge and awareness of self-management among diabetic patients in Saudi Arabia - Bakhuraysah, Maha M.; Alsalmi, Samar A.; Alfadli, Shahad N.; Alotaibi, Salha A.; Althomali, Dimah S.; Gharib, Amal F.; Alrehaili, Amani A.; Alhuthali, Hayaa M. (Jour Med Resh and Health Sci, 2022)
Background: The rate of diabetes mellitus (DM) around the world is increasing significantly, and is expected to upsurge to 578 million by 2030. According to World Health Organization (WHO), Saudi Arabia ranks the seventh in the world for the rate of DM. Thus, self-management is critical for controlling patient blood glucose levels and avoiding any serious complications. The aim of conducting this study was to measure the knowledge, and awareness of diabetic patients about the disease and perform self-management continuously. Methods: This study was conducted in Saudi Arabia, using a questionnaire filled out by 204 male and female with DM, who participated in the study.A cross-sectional investigation was led to assess knowledge, learning, and regular monitoring and self-management. Results: The result indicated that knowledge, attitudes, and practice were low, mild positive, and low respectively towards diabetic control and glucose monitoring among diabetic patients. 51% of the study participants had hyperglycemia, and about 16.7% used Glucophage as treatment. Although most of the participants 153 (75%) realized the importance of using a glucometer for monitoring their blood glucose levels and preventing further medical complications, few of them were following regular physical activity 73 (35.8%), a specific diet 62 (30.4%) and measuring the amount of daily intake of sugar 46 (22.5%). Conclusion: The research showed that participants with DM had knowledge and awareness of their disease but they did not perform self-management appropriately, despite the popularity and ease of glucometer use. The ongoing study is being undertaken to evaluate the validity of this questionnaire and by extension their awareness of the test reliability and accuracy using different types of machines; glucometer, i-STAT system, and another lab analyzer.